Regret as a political intervention : an essay in the historical anthropology of the early mongol's. - Humphrey, Caroline; Hürelabaatar, Altanhuu (Oxford GB: Oxford University Press)
Trata acerca del lamento como forma de intervención política de los mongoles. Aborda la cuestión moral y sibólica de este tipo de intervención.
Keywords: HISTORIA; ANTROPOLOGIA; POLITICA; MONGOLES